2013
DOI: 10.1186/1471-2474-14-155
|View full text |Cite
|
Sign up to set email alerts
|

Increase of chronic low back pain prevalence in a medium-sized city of southern Brazil

Abstract: BackgroundChronic low back pain (CLBP) is a highly disabling morbidity with high social, economic and individual effects. Demographic, occupational and behavioral changes that took place in Brazil over the last decade are related with an increasing burden of chronic conditions. Despite these changes, comparison studies on CLBP prevalence and associated factors, over time are scarce in the literature in general, and unknown in Brazil. The present study compared the CLBP prevalence in a medium sized city in Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
85
1
39

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(127 citation statements)
references
References 29 publications
2
85
1
39
Order By: Relevance
“…Studies with other aims have also described associations with education [40][41][42][43][44][45][46][47][48]. Studies assessing the prevalence of LBP reported associations with educational level, even though this was not their primary search goal [49][50][51][52][53][54][55][56][57][58]. Further studies having as their primary aim the investigation of the association of educational level attained or number of years of education with other variables are therefore needed to increase the number of studies eligible for meta-analysis that correlate education with the occurrence of LBP.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with other aims have also described associations with education [40][41][42][43][44][45][46][47][48]. Studies assessing the prevalence of LBP reported associations with educational level, even though this was not their primary search goal [49][50][51][52][53][54][55][56][57][58]. Further studies having as their primary aim the investigation of the association of educational level attained or number of years of education with other variables are therefore needed to increase the number of studies eligible for meta-analysis that correlate education with the occurrence of LBP.…”
Section: Discussionmentioning
confidence: 99%
“…Population-based studies have shown that CLBP prevalence ranges from 1.0 to 25.6%, with some studies suggesting an increasing prevalence in the general adult population. 4,5 In urban occupations, CLBP prevalence ranges from 1.8% among industry workers in Russia to 19.4% among civil servants in Brazil. 6,7 Only one study from Thailand reported CLBP prevalence of 46.3% among rice farmers.…”
Section: Introductionmentioning
confidence: 99%
“…5,15 Respondents reporting pain in the lumbar region were asked the following question: ''In the last year, have you continuously felt this pain for 3 months (90 days)?'' Subjects answering positively were considered to have CLBP.…”
mentioning
confidence: 99%
“…1 It constitutes an unpleasant sensory and emotional experience as a result of installed or potentialtissue injury, which can be characterised as a biopsychosocial disorder. 2 Low back pain affects approximately 80-85% of people around the world during their life and in developed countries is a major cause of disability in youth and young adults, being considered as one of the greatest contributors to sick leave [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%